A synergistic approach for the simultaneous decarbonisation of power and industry via bioenergy with carbon capture and storage (BECCS). (August 2019) - Cabral, Renato P.; Bui, Mai; Mac Dowell, Niall
Highlights: BECCS can result in negative emissions. Replacing the global coal fleet with BECCS could offset industrial emissions. A synergistic framework is required to enable this approach. Abstract: There is a need for a rapid and large scale decarbonisation to reduce CO2 emissions by 45% within 12 years. Thus, we propose a method that accelerates decarbonisation across multiple sectors via a synergistic approach with bioenergy with CCS (BECCS), which is able to remove 740 kg CO 2 from air per MWh electricity generated. Industry is a hard-to-decarbonise sector which presents a unique set of challenges where, unlike the power sector, there are no obvious alternatives to CCS. One of these challenges is the significant variation of CO2 concentration, which directly influences CO2 capture costs, ranging from $10/t CO 2 to over $170/t CO 2 for high (95–99% CO2 ) and low CO2 concentration (4% CO2 ) applications, respectively. Re-purposing the existing coal-fired power plant fleet into BECCS displaces CO2 emissions from coal-use and enables a just transition, i.e., avoiding job loss, providing a supportive economic framework that does not rely on government subsidies. Negative emissions generated from capturing and storing atmospheric CO2 can be converted into negative emission credits (NECs) and auctioned to hard-to-decarbonise sectors, thus providing another revenue stream to the power plant. A levelised cost of electricity (LCOE) between $70 and $100 per MWh can be achieved through auctioning NECs at $90–$135 per t CO 2 . Offsetting the global industrial CO2 emissions of 9 Gt CO 2 would require 3000 BECCS plants under this framework. This approach could jumpstart industrial decarbonisation whilst giving this sector more time to develop new CCS technologies.